Sports on Victoria's Park, St. Lucia - Unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2020)
People are seen at a sports day on Victoria's Park, in St. Lucia. They are well dressed for this event. Taken from the back of the postcard: TUCK'S POST CARD Carte Postale. Has seal in top left with words By Appointment underneath Published for Clarke & Co., Castries, St., Lucia, B.W.I Printed in the United Kingdom. Cost: £10 May joy reign in your heart, True happiness attend you, your birthday may peaceful be, and good fortune ne'er depart. With all kind thoughts & best wishes for your Birthday. From your mamma's servant Adeliade. To Master George.
Tuck's Post Card
Landscape, Black and White, 4 x 6 in.
Keywords: Sports; Tents; People; Palm trees; Activities; Recreation; Pavilions (Facilities); Clothing and dress; Sports day; Victoria Park - St. Lucia